Astrocyte-mediated inflammatory responses in traumatic brain injury: mechanisms and potential interventions - Zhang, Haifeng; Zhang, Xian; Chai, Yan; Wang, Yuhua; Zhang, Jianning; Chen, Xin (Frontiers in Immunology, 2025)
Astrocytes play a pivotal role in the inflammatory response triggered by traumatic brain injury (TBI). They are not only involved in the initial inflammatory response following injury but also significantly contribute to Astrocyte activation and inflammasome release are key processes in the pathophysiology of TBI, significantly affecting the progression of secondary injury and long-term outcomes. This comprehensive review explores the complex triggering mechanisms of astrocyte activation following TBI, the intricate pathways controlling the release of inflammasomes from activated astrocytes, and the subsequent neuroinflammatory cascade and its multifaceted roles after injury. The exploration of these processes not only deepens our understanding of the neuroinflammatory cascade but also highlights the potential of astrocytes as critical therapeutic targets for TBI interventions. We then evaluate cutting-edge research aimed at targeted therapeutic approaches to modulate pro-inflammatory astrocytes and discuss emerging pharmacological interventions and their efficacy in preclinical models. Given that there has yet to be a relevant review elucidating the specific intracellular mechanisms targeting astrocyte release of inflammatory substances, this review aims to provide a nuanced understanding of astrocyte-mediated neuroinflammation in TBI and elucidate promising avenues for therapeutic interventions that could fundamentally change TBI management and improve patient outcomes. The development of secondary brain injury and long-term neurological sequelae. By releasing a variety of cytokines and chemokines, astrocytes regulate neuroinflammation, thereby influencing the survival and function of surrounding cells. In recent years, researchers have concentrated their efforts on elucidating the signaling crosstalk between astrocytes and other cells under various conditions, while exploring potential therapeutic interventions targeting these cells. This paper highlights the specific mechanisms by which astrocytes produce inflammatory mediators during the acute phase post-TBI, including their roles in inflammatory signaling, blood-brain barrier integrity, and neuronal protection. Additionally, we discuss current preclinical and clinical intervention strategies targeting astrocytes and their potential to mitigate neurological damage and enhance recovery following TBI. Finally, we explore the feasibility of pharmacologically assessing astrocyte activity post-TBI as a biomarker for predicting acute-phase neuroinflammatory changes.